Cognitive Reactivity to Success and Failure Relate Uniquely to Manic and Depression Tendencies and Combine in Bipolar Tendencies. (7th December 2011) - Raes, Filip; Ghesquière, Ine; Van Gucht, Dinska
Abstract : The present study examined simultaneously the relations between cognitive reactivity to success and failure, on the one hand, and depression, manic, and bipolar tendencies, on the other hand. Participants (161 students) completed measures of success and failure reactivity, current manic and depressive symptoms, and tendencies towards depression, mania, and bipolarity. Results showed that respondents with a greater tendency towards depression evidenced greater (negative) reactivity to failure, whereas those with a greater tendency toward mania evidenced greater (positive) reactivity to success. Depression vulnerability was unrelated to success reactivity, and manic vulnerability was unrelated to failure reactivity. Tendencies toward bipolarity correlated significantly with both failure and success reactivity in a negative and positive manner, respectively. These findings add to the growing body of literature, suggesting that different features or cognitive tendencies are related to depression vulnerability versus manic vulnerability and imply that these "mirrored" cognitive features both form part of vulnerability to bipolar disorder.